Assessing protein‑energy wasting in chronic kidney disease - Verma, Shailvi (International Journal of Research in Medical Sciences, 2023)
Chronic kidney disease is often accompanied with a syndrome known as protein-energy wasting, which is defined by decreased protein consumption, protein loss due to metabolic disturbances, and physical consequences include sarcopenia and frailty. Due to population aging and advancements in the treatment of other chronic illnesses, this problem has drastically increased in recent years. The frequency of morbidity and death in chronic kidney disease patients may be greatly decreased with proper therapy of as protein-energy wasting. Therefore, it's crucial to prevent and manage as protein-energy wasting in chronic kidney disease patients by doing a thorough evaluation and offering each patient a customized, evidence-based treatment plan. Once protein-energy wasting is recognized, a nutritionist should be contacted to create a management strategy. A thorough diet specifically designed to fit the patient's requirements, any required nutritional supplements, and counselling about dietary changes, symptom management, and psychological support should all be part of this strategy. The risk of protein-energy wasting may be decreased with proper assessment and care. This includes changes to one's diet, resistance training or other forms of exercise, dialysis or organ transplantation when necessary, and drugs to treat any underlying disorders.